Effectiveness of non-auditory verbal therapies in improving speech production in school-aged hearing-impaired children: A critically appraised topic. Issue 1 (3rd April 2019) - White, Sarahlouise; Zhai, Ivy; McMinn, Claire
Abstract: A critically appraised topic (CAT) is one form of rapid review that can be particularly useful for informing practice (White, Raghavendra, & McAllister, 2017). The purpose of this CAT was to determine the effectiveness of non-auditory verbal therapies in improving speech production in school-aged children who are hearing impaired. In addition to the methodology, the authors present and discuss the findings of this CAT. The authors propose an update to this CAT in January 2020.